IGF1-Stimulated Posttraumatic Hippocampal Remodeling Is Not Dependent on mTOR - Littlejohn, Erica L.; DeSana, Anthony J.; Williams, Hannah C.; Chapman, Rudy T.; Joseph, Binoy; Juras, Jelena A.; Saatman, Kathryn E. (Frontiers in Cell and Developmental Biology, 2021)
Adult hippocampal neurogenesis is stimulated acutely following traumatic brain injury (TBI). However, many hippocampal neurons born after injury develop abnormally and the number that survive long-term is debated. In experimental TBI, insulin-like growth factor-1 (IGF1) promotes hippocampal neuronal differentiation, improves immature neuron dendritic arbor morphology, increases long-term survival of neurons born after TBI, and improves cognitive function. One potential downstream mediator of the neurogenic effects of IGF1 is mammalian target of rapamycin (mTOR), which regulates proliferation as well as axonal and dendritic growth in the CNS. Excessive mTOR activation is posited to contribute to aberrant plasticity related to posttraumatic epilepsy, spurring preclinical studies of mTOR inhibitors as therapeutics for TBI. The degree to which pro-neurogenic effects of IGF1 depend upon upregulation of mTOR activity is currently unknown. Using immunostaining for phosphorylated ribosomal protein S6, a commonly used surrogate for mTOR activation, we show that controlled cortical impact TBI triggers mTOR activation in the dentate gyrus in a time-, region-, and injury severity-dependent manner. Posttraumatic mTOR activation in the granule cell layer (GCL) and dentate hilus was amplified in mice with conditional overexpression of IGF1. In contrast, delayed astrocytic activation of mTOR signaling within the dentate gyrus molecular layer, closely associated with proliferation, was not affected by IGF1 overexpression. To determine whether mTOR activation is necessary for IGF1-mediated stimulation of posttraumatic hippocampal neurogenesis, wildtype and IGF1 transgenic mice received the mTOR inhibitor rapamycin daily beginning at 3 days after TBI, following pulse labeling with bromodeoxyuridine. Compared to wildtype mice, IGF1 overexpressing mice exhibited increased posttraumatic neurogenesis, with a higher density of posttrauma-born GCL neurons at 10 days after injury. Inhibition of mTOR did not abrogate IGF1-stimulated enhancement of posttraumatic neurogenesis. Rather, rapamycin treatment in IGF1 transgenic mice, but not in WT mice, increased numbers of cells labeled with BrdU at 3 days after injury that survived to 10 days, and enhanced the proportion of posttrauma-born cells that differentiated into neurons. Because beneficial effects of IGF1 on hippocampal neurogenesis were maintained or even enhanced with delayed inhibition of mTOR, combination therapy approaches may hold promise for TBI.